Avoiding Damage of CO2 Injection Wells Caused by Temperature Variations. (July 2017) - Torsæter, M.; Todorovic, J.; Lavrov, A.; Gawel, K.; Lund, H.; Roy, P.; Carroll, S.
Abstract: Well integrity is a prerequisite for safe geological storage of CO2 . Both active and abandoned wells are man-made channels between the storage reservoir and the atmosphere that can become leakage paths over time. The CO2 injection wells are of special concern, as they are exposed to low temperatures and strong temperature variations. In oil/gas wells this is known to threaten well integrity, and it should therefore be investigated how the sealing ability of well barriers is affected in the temperature range relevant for CO2 injection wells. This has been the main focus in a research project entitled "Ensuring well integrity during CO2 injection" carried out in the period 2014-2016. This paper summarizes the major findings obtained within the project, and presents research-based recommendations for construction and operation of CO2 injection wells.